South Polar chart / published at the Admiralty, 20th May, 1887
New edition April 1910. Small corrections . [19]10. Relief shown by spot heights and hachures. Depths shown by soundings.; Includes "Explanation of the tracks" showing 23 explorer routes.; Annotations in colored pencil.; "83.14" -- upper right margin. Color;